ANALISIS PENGARUH KEPUASAN PASIEN RAWAT JALAN TERHADAP PENGGUNAAN APLIKASI TELEKONSULTASI PADA MASA PANDEMI COVID-19 DI RUMAH SAKIT STELLA MARIS MAKASSAR TAHUN 2022 - Rhezia Triwardani Sahlendar Asthan; Dian Ekawati; Afriyana Amelia N; Zulkifli Zulkifli (Jurnal Penelitian Kesehatan Pelamonia Indonesia, 2024)
Hospital is a health service institution that provides complete individual health services (health services that include promotive, preventive, curative, and rehabilitative) that provide inpatient, outpatient and emergency services. hospitals as institutions that require applications aimed at patients that can be used online such as teleconsultation. teleconsultation is one part of telemedicine so that its scope is narrower, while telemedicine is only an online consultation. The type of research used in this study is a type of quantitative research with a cross sectional study approach. The population in this study were patients using the teleconsultation application at the Stella Maris Hospital Makassar. The number of teleconsultation application users at Stella Maris Hospital is 150 patients in 2021. The sample in this study is teleconsultation of patients at Stella Maris Hospital Makassar. The sampling technique used in this study is probability sampling and the sampling method is accidental sampling. The analysis technique used univariate analysis and bivariate analysis. The results showed that there was a relationship between access to health services and hospital teleconsultation (P=0.039), there was no relationship between the quality of health services and hospital teleconsultation (P=0.759), there was a relationship between the health service process and hospital teleconsultation (P=0.759). (P = 0.020), there is a relationship between the health service system and hospital teleconsultation (P = 0.047). It is recommended to the hospital to further improve the health service system on the teleconsultation application at the Stella Maris Hospital so that it is easier for patients or their families to use the application.